Planning for health equity in the Americas: an analysis of national health plans - Matthew M. Kavanagh; Laura Fernanda Norato; Eric A. Friedman; Adria N. Armbriste (Pan American Health Organization, 2021)
There is growing recognition that health and well-being improvements have not been shared across populations in the Americas. This article analyzes 32 national health sector policies, strategies, and plans across 10 different areas of health equity to understand, from one perspective, how equity is being addressed in the region. It finds significant variation in the substance and structure of how the health plans handle the issue. Nearly all countries explicitly include health equity as a clear goal, and most address the social determinants of health. Participatory processes documented in the development of these plans range from none to extensive and robust. Substantive equity-focused policies, such as those to improve physical accessibility of health care and increase affordable access to medicines, are included in many plans, though no country includes all aspects examined. Countries identify marginalized populations in their plans, though only a quarter specifically identify Afro-descendants and more than half do not address Indigenous people, including countries with large Indigenous populations. Four include attention to migrants. Despite health equity goals and data on baseline inequities, fewer than half of countries include time-bound targets on reducing absolute or relative health inequalities. Clear accountability mechanisms such as education, reporting, or rights-enforcement mechanisms in plans are rare. The nearly unanimous commitment across countries of the Americas to equity in health provides an important opportunity. Learning from the most robust equity-focused plans could provide a road map for efforts to translate broad goals into time-bound targets and eventually to increasing equity.